RINGKASAN DISERTASI RAKYAT MISKIN DAN PEREBUTAN RUANG KOTA DI SURABAYA TAHUN 19001960-an - Purnawan Basudoro (Masyarakat Indonesia, 2012)
Surabaya is one of urban destinations for people coming from its surrounding area toseek livelihood. From time to time, the number of city dwellers increases continuously.At the same time, the city is also expanded. This condition affects the waysthe pooraccess city space to reside. Poor people do not have access to city space legally. Inorder to survive in the city, they often took over the city space ilegally. The poorhastostruggle in various ways in order to obtain space to live in Surabaya. This paperreveals the struggle of the poor for accessing city space in Surabaya.The city wasdeveloped to be the center of government and the center of leading industry andbusiness in Indonesia, all at once. Since the early twenty century until 1960s, thestruggle for cityspace in Surabaya involving the poor can be divided into two periods.Firstly, defensive period, which went on until the infiltration of Japan inIndonesia. Inthis period the struggle forcity space involved the poor, landlords and gemeente (municipality). The struggle for cityspace happened at private lands. Secondly, offensiveperiod, which went on since the beginning of Indonesias independence until the 1960s.In this period the struggle for cityspace had extended to public spaces involving thepoor, City Government and other communities.Keywords: poor people, city space, Surabaya